Effect of Serine and Methionine on Electrochemical Behavior of the Corrosion of Mild Steel in Aqueous Solutions. (6th March 2013) - Rahuma, Mohamed N.; EL-Sabbah, Mohamed B.; Hamad, Imperiyka M.
Abstract : The pitting corrosion behaviour of mild steel in Na2 HPO4 solutions contains chloride ion as an aggressive ion and serine and methionine as inhibitors were investigated using open-circuit potential (OCP), potentiodynamic polarization measurements, and pitting corrosion current measurements; both inhibitors shift the potential in the positive direction. The corrosion rate of the mild steel was measured in the absence and presence of the inhibitors, and the inhibition efficiency of the amino acids at a concentration of 0.02 M was calculated. The pitting corrosion current shows that increasing concentration of the inhibitor causes a decrease in pitting current density, and inhibition efficiency increases with increasing concentration of the inhibitors. The adsorption of these inhibitors on the mild steel surface obeys Langmuir isotherm, and the calculated adsorption free energy (ΔG a d s 0 ) for the inhibitors on the mild steel in 0.1 M (Na2 HPO4 + NaCl) solutions was found to be (−24.61, −29.34) kJ/mol for serine and methionine, respectively, which reveals strong physical adsorption of the amino acids molecules on the mild steel surface.